Data warehousing Concepts, techniques, products and application - Prabhu, C.S.R (PHI Learning, 2008)
The third edition of this well-received text analyses the fundamental concepts of data warehousing, data marts, and OLAP. The author discusses, in an easy-to-understand language, important topics such as data mining, how to build a data warehouse, and potential applications of data warehousing technology in government. Besides, the text compares and contrasts the currently available software tools used to design and develop data warehouses.